Consensus statement on the diagnosis and treatment of sclerosing diseases of the skin, Part 2: Scleromyxoedema and scleroedema - Knobler, Robert; Geroldinger-Simić, Marija; Kreuter, Alexander; Hunzelmann, Nicolas; Moinzadeh, Pia; Rongioletti, Franco; Denton, Christopher; Mouthon, Luc; Cutolo, Maurizio; Smith, Vanessa; Gabrielli, Armando; Bagot, Martine; et al. (Journal of the European Academy of Dermatology and Venereology, 2024)
The term ‘sclerosing diseases of the skin’ comprises specific dermatological entities, which have fibrotic changes of the skin in common. These diseases mostly manifest in different clinical subtypes according to cutaneous and extracutaneous involvement and can sometimes be difficult to distinguish from each other. The present consensus provides an update to the 2017 European Dermatology Forum Guidelines, focusing on characteristic clinical and histopathological features, diagnostic scores and the serum autoantibodies most useful for differential diagnosis. In addition, updated strategies for the first- and advanced-line therapy of sclerosing skin diseases are addressed in detail. Part 2 of this consensus provides clinicians with an overview of the diagnosis and treatment of scleromyxoedema and scleroedema (of Buschke).
CRIS-Team Scopus Importer:2024-04-12